2018
DOI: 10.1038/s41598-018-29966-7
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary studies on a sick-leader syndrome-associated mass stranding of sperm whales (Physeter macrocephalus) along the Adriatic coast of Italy

Abstract: Mass strandings of sperm whales (Physeter macrocephalus) are rare in the Mediterranean Sea. Nevertheless, in 2014 a pod of 7 specimens stranded alive along the Italian coast of the Central Adriatic Sea: 3 individuals died on the beach after a few hours due to internal damages induced by prolonged recumbency; the remaining 4 whales were refloated after great efforts. All the dead animals were genetically related females; one was pregnant. All the animals were infected by dolphin morbillivirus (DMV) and the preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 85 publications
0
29
0
Order By: Relevance
“…On the opposite, cephalopods belonging to the Histioteuthidae family represent the main diet of sperm whales 54 , 55 and to follow those belonging to the Architeuthis genus. Interestingly, Bustamante et al 56 , have found high concentrations of Cd, Co, Cu and Se bioaccumulated in the digestive gland of Architeuthis dux from the Mediterranean and Atlantic Spanish waters, whereas high concentrations of As, Co, Hg, Ni, and Se were also found in branchial hearts.…”
Section: Discussionmentioning
confidence: 99%
“…On the opposite, cephalopods belonging to the Histioteuthidae family represent the main diet of sperm whales 54 , 55 and to follow those belonging to the Architeuthis genus. Interestingly, Bustamante et al 56 , have found high concentrations of Cd, Co, Cu and Se bioaccumulated in the digestive gland of Architeuthis dux from the Mediterranean and Atlantic Spanish waters, whereas high concentrations of As, Co, Hg, Ni, and Se were also found in branchial hearts.…”
Section: Discussionmentioning
confidence: 99%
“…An hypothesis may be that the NE-Atlantic strain was introduced in the Mediterranean Sea in 2014 by the www.nature.com/scientificreports/ Strait of Gibraltar, known to be an area of contact between cetaceans from the two seas. The pod that was found stranded on the Adriatic shores of Italy 3,30,31 may have come into contact with a carrier pod from the Atlantic Ocean 32 . Either Globicephala melas and Stenella coeruleoalba may have introduced of the NE-Atlantic strain to the naive cetacean population of the Mediterranean Sea, due to their well documented roles as DMV carriers 8,33 .…”
Section: Discussionmentioning
confidence: 99%
“…Habitat degradation, interaction with fisheries, and climate change are considered important issues interfering with the conservation of cetaceans worldwide [ 5 , 6 , 7 ]. Indeed, in the last decades the frequency of cetacean unusual mortality and stranding events has increased worldwide, including in the Mediterranean Sea [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%